Paving the way of entrepreneurship for university students: the role of innovativeness, technological adaptability, and self-management, with risk-taking and family support as moderator - Md. Abu Issa Gazi; Anika Tasnim Mim; Abdullah Al Masud; Md. Kazi Hafizur Rahman; Mohammad Bin Amin; Abdul Rahman bin S Senathirajah; Judit Oláh (Cogent Education)
This study aims to examine how entrepreneurial education (EE), innovativeness (INT), technological adaptability (TA), and self-management (SM) shape the risk-taking behavior (RTB) and intention to become entrepreneurs of university students. Additionally, it intends to explore the influence of risk-taking behavior (RTB) as a mediator and family support (FS) as a moderator. This study utilized a quantitative methodology to gather data from a cohort of 396 university students. The data was collected by a survey questionnaire that employed a seven-point Likert scale. The sampling method used was convenience sampling. We utilized structural equation modeling (SEM) to examine and interpret the data. The findings demonstrated a direct relationship between each independent variable and risk-taking behavior as well as entrepreneurial intentions. The proposed variable and entrepreneurial intentions are significantly mediated by risk-taking behavior. Furthermore, there is a favorable correlation between risk-taking behavior and entrepreneurial intention when family support is present. This study covers literature gaps on entrepreneurial intentions by thoroughly investigating interconnected variables including self-management, innovativeness, technological adaptability, risk-taking behavior, and entrepreneurial intentions. The study evaluates the impact of these determinants, explores risk-taking behavior as a possible mediator, and explores the moderating effects of family support.